Student activities and their role in promoting citizenship values for students at the Universities of Northern Borders and Hafar Al-Batin in the Kingdom of Saudi Arabia - Bani Naser, Ala'a (Journal of Educational and Psychological Sciences, 2021)
The aimed of this study to identify the role of student activities in promoting citizenship values in Saudi universities, and it developed an instrument consisting of (28) items, distributed into two areas: the role of student activities in strengthening citizenship values, and a positive practice that develops citizenship values through student activities, and applied the study instrument on a sample consisted of (548) students from the Universities of Hafr Al-Batin and the Northern Borders, and the sample was chosen by the stratified random method. The results of the study showed that the role of student activities in promoting citizenship values came to a high degree as it came at my average calculation. (3.93), where the role of student activities in consolidating citizenship values came in first place with a computational average (3.95), while the field of "positive practice that develops citizenship values through student activities" came with an average calculation (5.0:3.91), as well as statistically significant differences in the gender variant in favor of males on average (3.91), the university variant was in favor of the Northern Border University with a computational average (3.86), and no differences were shown between the type of college in which the student taught.